2008
DOI: 10.1108/sd.2008.05624fad.001
|View full text |Cite
|
Sign up to set email alerts
|

North American business strategies towards climate change

Abstract: Business has become a key part of the fabric of global environmental governance, considered here as the network which orders and regulates economic activity and its impacts. We argue that businesses generally are willing to undertake limited measures consistent with a fragmented and weak policy regime. Further, the actions of businesses act to create, shape and preserve that compromised regime. We examine three types of indicators of business responses in North America: ratings by external organizations, commi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
110
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(113 citation statements)
references
References 7 publications
2
110
0
1
Order By: Relevance
“…This observation is consistent with existing literature (e.g. Derber 2010; Jones and Levy 2007;Lohmann 2011;Sapinski 2015) and indicates that despite their emergence within distinct sections of the corporate elite, climate capitalism and carboniferous capitalism may share similar long term goals.…”
Section: Discussionsupporting
confidence: 81%
“…This observation is consistent with existing literature (e.g. Derber 2010; Jones and Levy 2007;Lohmann 2011;Sapinski 2015) and indicates that despite their emergence within distinct sections of the corporate elite, climate capitalism and carboniferous capitalism may share similar long term goals.…”
Section: Discussionsupporting
confidence: 81%
“…According to some studies, companies with the worst performance appear to divulge the greatest amount of information (e.g., Cowan and Deegan 2011;Prado-Lorenzo and Garcia-Sanchez 2010). A significant gap also seems to exist between the real commitment of companies and their public image (Jones and Levy 2007;Nyberg et al 2013;Saeverud and Skjaerseth 2007;Skjaerseth and Skodvin 2001). However, few studies have examined the justifications that big polluters produce to legitimize their operations and their impacts in the area of climate change.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, they challenged the findings of climate science and emphasized the potentially disastrous economic consequences of policies to be adopted in this area. European companies were generally much more receptive to regulations and more willing to invest in green technologies (Jones and Levy 2007;Levy and Egan 2003;Schlichting 2013). Levy and Egan (2003) have analyzed the war of position that companies in the oil and automotive sectors engage in to influence climate regulations.…”
Section: Political Activitiesmentioning
confidence: 99%
“…The pattern of target-setting across the sectors can be attributed to operational and regulatory factors pertaining to specific sectors. Sectors that are less carbon-intensive in operations (e.g., Diversified Financials, Consumer Durables & Apparel, Food & Staples Retailing, and Software & Services) are less likely to be threatened by regulatory and market pressures [44]. Since regulatory and market risks are instrumental in driving environmental practices [44,45], it can be expected that less carbon-intensive sectors lag behind in using emission targets.…”
Section: Resultsmentioning
confidence: 99%
“…Firms in these two sectors produce the final goods (e.g., cosmetics, food products, drinks) and hence are in closer contact with consumers than firms in the upstream value chain. Decreasing consumer demand for carbon-intensive products has been argued to be one of the primary risks for firms [44], and firms in closer contact with consumers naturally bear greater pressure from the consumers to improve environmental friendliness. Indeed, the literature has shown that being a final goods producer has a significant and positive effect on environmental practices [45].…”
Section: Target Adoption and Target Metricmentioning
confidence: 99%